BATS - Faisal Ali, Anwarali Khan; Muhd Amsyari, Morni; Julius Willian, Dee; Norfarhana, Mazlan; Wan Nur Syafinaz, Wan Azman; Emy Ritta, Jinggong; Nur Afi qah Aqilah, Azhar; Roberta Chaya Tawie, Tingga; Mohd Ridwan, Abd Rahman; Isham, Azhar (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
A hundred species of bats, representing nine families, are now known from Borneo. Classifi ed as either frugivorous, nectarivorous or insectivorous feeder, their diets permit them to play important roles in the maintenance of ecosystem functions and dynamics, through their action as seed dispersers, pollinators and regulators of insect populations. Of these, the insectivorous bats of the families Hipposideridae, Rhinolophidae and Vespertilionidae contribute the most to species numbers.